Plasma Multiplatform Metabolomics Towards Evaluation of Gender Differences in Pulmonary Arterial Hypertension—A Pilot Study - Renata Wawrzyniak; Tamara Gaillard; Margot Biesemans; Bożena Zięba; Ewa Lewicka; Michał Markuszewski; Alicja Dąbrowska-Kugacka (Biomedicines, 2025)
Background: Pulmonary arterial hypertension (PAH) is a rare and severe condition characterized by increased pulmonary arterial pressure and vascular resistance. Women are more susceptible to PAH yet have higher survival rates than men, a phenomenon called the “estrogen paradox”. This study aims to investigate the sex-based differences in PAH using plasma untargeted metabolomics. Methods: Plasma samples were collected from 43 PAH patients and 37 healthy controls. The samples were analyzed using two complementary analytical techniques: gas chromatography–mass spectrometry (GC-QqQ/MS) and liquid chromatography–mass spectrometry (LC-Q-ToF/MS). The metabolic differences between male and female PAH patients and controls were identified using multivariate statistical analyses. Results: Our results show changes in the lipid, fatty acid, and amino acid metabolism in both sexes. Women presented additional changes in the carbohydrate, bile acid, and nucleotide metabolism. The metabolites affected by PAH in women included decreased threonine, tryptophan, and lipid intermediates and elevated bile acids. Men were found to have additional changes in the heme catabolism, cholesterol synthesis, and lipoxygenase pathways. The metabolites affected by PAH in men included decreased branched-chain amino acids and increased bilirubin, phospholipids, and oxidized fatty acids. Conclusions: The gender differences observed in the development of PAH are likely multifactorial. While estrogens and potentially other sex hormones have been implicated in modulating relevant biological pathways, their exact role in disease progression and pathogenesis remains to be fully elucidated. The specific metabolic changes in women and men point to distinct disease mechanisms, potentially explaining the differences in prevalence, prognosis, and treatment response of patients with PAH. The obtained results should be validated with the use of targeted quantitative analyses and larger numbers of patients.